Combatting Slums, Suistaining Poverty: Dynamic Urban Governance in Makassar, Indonesia - Andi Luhur Prianto; Andi Annisa Amalia (Otoritas : Jurnal Ilmu Pemerintahan, 2019)
Urban livelihood asset is an accumulation of labor capital and financial capital. The existence of a slum area in the coastal area of Untia with an area of 7.13 ha of 740.10 ha of the total slum area in the city of Makassar. This area is a potential strategic accumulation of livelihoods in the human capital, institutional, physical, financial and environmental resources, but on the other hand also has a high level of vulnerability. This study aims to obtain an empirical situation regarding the lives of poor people in the slums of the Untia coastal area, Makassar City. The socio-economic conditions of the community, the use of space, the ownership status of land and buildings, the condition of infrastructure and facilities of settlements in coastal slums as a basis for the reconstruction of coastal slums handling models based on dynamic governance. The findings show that urban slum in coastal areas are very rapidly growing. Problems that continue along with various programs carried out by the government. All programs by the state and non-state have been carried out in an effort to eradicate slum areas, but in fact the poverty rate in the region continues to increase. Managing a slums settlement program can use a dynamic governance framework: thinking ahead, thinking again, and thinking across. All of these strategies have been internalized of digital information and communication technology.